2014
DOI: 10.3389/fphys.2014.00295
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of NK cells and monocytes in vascular inflammation and myocardial infarction

Abstract: Inflammatory monocytes and macrophages have been identified as key players in the pathogenesis of atherosclerosis, arterial hypertension, and myocardial infarction (MI). They become powerful mediators of vascular inflammation through their capacity to secrete and induce the production of proinflammatory cytokines, chemokines and adhesion molecules and through the production of reactive oxygen species mainly via their NADPH oxidase. Importantly, a crosstalk exists between NK cells and monocytes that works via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 68 publications
2
39
0
1
Order By: Relevance
“…14 Also, Kaya et al showed that soluble CD40 ligand was elevated in acute PE. 23 Cytokines and several proteins such as monocyte chemoattractant protein-1 (MCP-1), CCL2, interferon-inducible protein (IP-10; CXCL10), interleukin-8 cause the migration of monocytes into the vascular wall, subsequent endothelial dysfunction, impact on nitric oxide and endothelin-1 and smooth muscle cell proliferation. Moreover, these data may support the role of inflammation in acute PE.…”
Section: Discussionmentioning
confidence: 99%
“…14 Also, Kaya et al showed that soluble CD40 ligand was elevated in acute PE. 23 Cytokines and several proteins such as monocyte chemoattractant protein-1 (MCP-1), CCL2, interferon-inducible protein (IP-10; CXCL10), interleukin-8 cause the migration of monocytes into the vascular wall, subsequent endothelial dysfunction, impact on nitric oxide and endothelin-1 and smooth muscle cell proliferation. Moreover, these data may support the role of inflammation in acute PE.…”
Section: Discussionmentioning
confidence: 99%
“…Although the link between type I interferon and NK cells in controlling corneal HSV-1 infection is not clear, it is reported that in vaccinia viral infection, Type I interferon action on NK cells enhance its effector function and thereby help the NK cells in promoting the viral clearance from infected tissues (33). Similarly, interplay between NK cells and inflammatory monocytes has recently been shown to promote vascular inflammation (34). It is possible that collective interactions between type I interferon, NK cells and inflammatory monocytes help in effectively controlling HSV-1 load in cornea at early time-point post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Crosstalk between monocytes and NK cells infiltrating the infarcted tissue can drive a T-bet/IFNγ/IL-12 signaling loop that results in the activation of both cellular populations and the increased recruitment of other inflammatory cells. Furthermore, this crosstalk was required for angiotensin-II induced vascular injury [10, 72]. …”
Section: Heart Disease Accompanied By Inflammationmentioning
confidence: 99%
“…However, blockade of NK cells and their receptors can protect against inflammation and damage in animal models of cardiac injury and inflammation. In these models, NK cells suppress the maturation and trafficking of inflammatory cells, alter the local cytokine and chemokine environments, and induce apoptosis in nearby resident and hematopoietic cells [1, 9, 10]. This review will dissect each protective mechanism employed by NK cells and explore how their properties might be exploited for their therapeutic potential.…”
mentioning
confidence: 99%